Making Sense of Online Classes during Quarantine due to the COVID-19 Pandemic: Students’ Perceptions from a Philippine University - Aguilar, Maria Virginia; Torres, Genine (Asia Social Issues, 2021)
Understanding students’ experiences towards online learning can help in devising innovative pedagogical approaches and creating effective online learning spaces. This study aimed to solicit the perception of 80 undergraduate students in one of the leading private institutions in the Philippines towards the compulsory shift from a blended to fully online learning modality amidst the novel coronavirus (COVID-19) pandemic. The study used a descriptive research design involving online surveys which contained Likert scale items and open-ended questions assessing one’s capacity for and the challenges to online learning, as well as the proposed recommendations for enhancing the overall online class experience. Descriptive statistics was used to group data across different subsets. Likewise, a content analysis of qualitative variables of the actual experiences of online classes using the school’s learning management system was prepared. Results indicate four self-perceived challenges in online learning: technological and infrastructural difficulties, individual readiness, instructional struggles, and domestic barriers. The study recommends re-evaluation and modification of current online learning guidelines to address the aforesaid challenges and build a genuinely resilient model for technology-driven and care-centered education based on student recommendations and challenges experienced.